Epigenomics as Potential Tools for Enhancing Magnitude of Breeding Approaches for Developing Climate Resilient Chickpea - Chandana, B. S.; Mahto, Rohit Kumar; Singh, Rajesh Kumar; Ford, Rebecca; Vaghefi, Niloofar; Gupta, Santosh Kumar; Yadav, Hemant Kumar; Manohar, Murli; Kumar, Rajendra (Frontiers in Genetics, 2022)
Epigenomics have become a significant research interest at a time when rapid environmental changes are occurring. Epigenetic mechanisms mainly result from systems like DNA methylation, histone modification, and RNA interference. Epigenetic mechanisms are gaining importance in classical genetics, developmental biology, molecular biology, cancer biology, epidemiology, and evolution. Epigenetic mechanisms play important role in the action and interaction of plant genes during development; epigenomic mechanisms also have impact on classical plant breeding programs, inclusive of novel variation, single plant heritability, hybrid vigour, plant-environment interactions, stress tolerance, and performance stability. The epigenetics and epigenomics may be significant for crop adaptability and pliability to ambient alterations, directing to the creation of stout climate-resilient elegant crop cultivars. In this review, we have summarised recent progress made in understanding the epigenetic mechanisms in plant responses to biotic and abiotic stresses and have also tried to provide the ways for the efficient utilization of epigenomic mechanisms in developing climate-resilient crop cultivars, especially in chickpea, and other legume crops.